Malnutrition and Economic growth, Dynamic panel data analysis of developing countries - Nafti, Sawssen (Technium Social Sciences Journal, 2021)
This paper concentrates on the empirical analysis of the pace of change in the food security situation in developing countries. We used dynamic panel data modeling by the GMM technique of Blundel and Bond (1998) during the period which range from 1990-2018 in order to estimate the relationship between the growth rate of GDP per capita and the growth rate of under nutrition prevalence in 26 developing countries belonging to the three different regions, namely Latin America, Sub-Saharan Africa and Asia. Food security was used at a national level as measured by the prevalence of under nutrition and the magnitude of the food deficit. The results of the estimates clearly show a negative relationship between economic growth rate and under nutrition prevalence; however, the economic growth of developing countries seems to be a key factor in reducing poverty and the proportion of the undernourished population.